Negative electrode material, preparation method of negative electrode material, negative electrode plate and battery
By using a combination of porous carbon support and nanosilicon particles in the battery negative electrode material and covering the resin layer on the porous carbon surface, the problem of silicon negative electrode material being easily reacted with water in the air under fast charging is solved, and the circulation and safety performance of the battery are improved.
Patent Information
- Application Number
- CN202311228171.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-21
- Publication Date
- 2025-03-21
AI Technical Summary
Silicon, as the negative electrode material of the battery, is prone to react with water in the air under fast charging, resulting in a degradation of circulation performance and may cause safety accidents.
Porous carbon is used as a support, and the nanosilicon particles are dispersed in the porous carbon pores, and the resin layer is covered on the porous carbon surface. A gap is provided between the resin layer and the outer surface of the porous carbon to reduce the enrichment of the nanosilicon particles and the opportunity to contact with air.
By reducing the chance of nanosilicon particles contacting air, the probability of reaction with water is reduced, the cycle performance and safety performance of the battery is improved, while the expansion space is reserved to reduce stress concentration and prolong the cycle life.
Smart Images

Figure CN119673982A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of negative electrode materials, and in particular to a negative electrode material, a method for preparing the negative electrode material, a negative electrode sheet and a battery. Background Art
[0002] As the pace of life accelerates, the pursuit of charging speed and battery life is getting higher and higher. However, the battery capacity will be significantly reduced during fast charging.
[0003] Silicon as a negative electrode material for batteries has a very high theoretical gram capacity of about 4200mAh / g, which is 10 times that of graphite, significantly improving the battery capacity. However, silicon negative electrode materials are nanomaterials, and their large specific surface area makes it easy to react with water in the air to produce a large amount of gas, which seriously affects the battery cycle performance and even causes safety accidents such as battery explosions. Summary of the invention
[0004] The present application provides a negative electrode material, a method for preparing the negative electrode material, a negative electrode plate and a battery, which can improve the safety performance of the battery.
[0005] The present application provides a negative electrode material, comprising:
[0006] Porous carbon;
[0007] Nano silicon particles dispersed in the pores of the porous carbon;
[0008] A resin layer covers the porous carbon, and a gap is provided between the resin layer and the outer surface of the porous carbon.
[0009] Furthermore, the gap is greater than or equal to 100 nm and less than or equal to 600 nm.
[0010] Furthermore, the resin layer is provided in one or more layers, and the thickness of a single layer of the resin layer is greater than or equal to 20 nm and less than or equal to 500 nm.
[0011] Furthermore, the material of the resin layer includes polyethylene, polyvinyl chloride, polypropylene, polystyrene, acrylonitrile-butadiene-styrene copolymer, natural rubber, styrene-butadiene rubber, nitrile rubber, ethylene-propylene rubber, silicone rubber, polyacrylonitrile, polyacrylic acid, sodium carboxymethyl cellulose, polyvinyl alcohol, epoxy resin, phenolic resin, polyester, unsaturated polyester resin, polyurethane and at least one low-carbon oil-based ester of the above resin derivatives.
[0012] Further, the Dv50 of the nano-silicon particles is greater than or equal to 5nm and less than or equal to 80nm; and / or, the spacing A between the nano-silicon particles is greater than or equal to 1nm and less than or equal to 20nm; and / or, the negative electrode material includes a silicon-carbon material, the silicon-carbon material includes the porous carbon and nano-silicon particles dispersed in the pores of the porous carbon, and the Dv50 of the silicon-carbon material is greater than or equal to 5nm and less than or equal to 10nm; and / or, the filling degree of the nano-silicon particles in the porous carbon is greater than or equal to 40% and less than or equal to 80%; and / or, the diameter of the pores of the porous carbon is greater than or equal to 5nm and less than or equal to 10nm; and / or, the thickness of the porous carbon is greater than or equal to 1nm and less than or equal to 3nm.
[0013] The present application also provides a method for preparing a negative electrode material, comprising:
[0014] dispersing nano-silicon particles in the pores of porous carbon to form a silicon-carbon material;
[0015] A resin layer is coated on the porous carbon, with a gap being provided between the resin layer and the outer surface of the porous carbon.
[0016] Furthermore, the step of dispersing nano-silicon particles in the pores of porous carbon to form a silicon-carbon material comprises:
[0017] Nano silicon particles are deposited in the pores of the porous carbon by vapor deposition.
[0018] Furthermore, the step of covering the porous carbon with a resin layer, with a gap between the resin layer and the outer surface of the porous carbon, comprises:
[0019] The prepared silicon carbon material is subjected to secondary vapor deposition, and a resin layer is deposited on the outer surface of the porous carbon to cover the porous carbon.
[0020] The embodiment of the present application also provides a negative electrode plate, comprising the above-mentioned negative electrode material or the negative electrode material prepared by the above-mentioned method.
[0021] Furthermore, the negative electrode plate includes a conductive agent, an adhesive and a negative electrode current collector, and a slurry formed by stirring the negative electrode material, the conductive agent and the adhesive is coated on the negative electrode current collector.
[0022] Furthermore, the thickness of the negative electrode sheet after rolling is greater than or equal to 20um and less than or equal to 50um, and the thickness of the negative electrode sheet after chemical formation is greater than or equal to 24 and less than or equal to 60um.
[0023] The embodiment of the present application also provides a battery, comprising a positive electrode plate and the above-mentioned negative electrode plate.
[0024] The surface of the porous carbon of the negative electrode material of the embodiment of the present application is covered with a resin layer, which is beneficial to reducing the enrichment of surface nano-silicon particles, reducing the probability of nano-silicon particles reacting with water when in contact with air, improving side reactions such as gas production after cycling, and improving the safety performance of the battery; a gap is provided between the resin layer and the outer surface of the porous carbon, and during the battery charging and discharging process, expansion space is reserved for the nano-silicon particles, reducing stress concentration and reducing the breakage of the nano-silicon particles during the cycle, thereby improving the cycle life; at the same time, the cycle expansion force is reduced, thereby improving the performance and life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 is a schematic diagram of a negative electrode material according to an embodiment of the present application;
[0026] Figure 2 yes Figure 1 Flow chart of the preparation method of negative electrode material shown. DETAILED DESCRIPTION
[0027] Exemplary embodiments will be described in detail herein, examples of which are shown in the accompanying drawings. When the following description refers to the drawings, the same numbers in different drawings represent the same or similar elements unless otherwise indicated. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present application. Instead, they are merely examples of devices consistent with some aspects of the present application as detailed in the appended claims.
[0028] The terms used in this application are only for the purpose of describing specific embodiments and are not intended to limit this application. Unless otherwise defined, the technical terms or scientific terms used in this application should be understood by people with ordinary skills in the field to which this application belongs. The words "first", "second" and similar words used in the specification and claims of this application do not indicate any order, quantity or importance, but are only used to distinguish different components. Similarly, words such as "one" or "one" do not indicate a quantitative limit, but indicate that there is at least one. "Multiple" or "several" means two or more. Unless otherwise specified, words such as "front", "rear", "lower" and / or "upper" are only for the convenience of explanation and are not limited to one position or one spatial orientation. Words such as "include" or "comprise" mean that the elements or objects appearing in front of "include" or "comprise" include the elements or objects listed after "include" or "comprise" and their equivalents, and do not exclude other elements or objects. Words such as "connect" or "connected" are not limited to physical or mechanical connections, and can include electrical connections, whether direct or indirect. The singular forms "a", "said" and "the" used in this specification and the appended claims are also intended to include the plural forms, unless the context clearly indicates otherwise. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more of the associated listed items.
[0029] The negative electrode material of the implementation mode of the present application can be applied to the negative electrode plate of the battery, and can also be applied to other products. The present application does not limit the application scenario of the negative electrode material.
[0030] See also Figure 1 As shown, the negative electrode material comprises: a silicon-carbon material 1 and a resin layer 2. The silicon-carbon material 1 comprises porous carbon 11 and nano-silicon particles 12 dispersed in the pores 111 of the porous carbon 11.
[0031] Optionally, the nano-silicon particles 12 are uniformly dispersed in the pores 111 of the porous carbon 11 .
[0032] Optionally, the porous carbon 11 includes at least one of hard carbon, soft carbon, carbon black, graphite, carbon fiber, vapor-grown carbon fiber, carbon nanotube, and graphene.
[0033] The resin layer 2 covers the porous carbon 11, which is beneficial to reduce the enrichment of surface nano-silicon particles 12, reduce the probability of nano-silicon particles 12 reacting with water when in contact with air, improve side reactions such as gas production after circulation, and enhance the safety performance of the battery; at the same time, the resin layer 2 can also enhance the conductivity.
[0034] A gap is provided between the resin layer 2 and the outer surface of the porous carbon 11, which reserves expansion space for the nano-silicon particles 12 during the battery charging and discharging process, reduces stress concentration, and reduces the breakage of the nano-silicon particles 12 during the cycle process, thereby improving the cycle life; at the same time, reduces the cycle expansion force, thereby improving the performance and life of the battery.
[0035] The gap D is greater than or equal to 100nm and less than or equal to 600nm. Specifically, the gap D can be 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, etc. Of course, it can also be other values within the above range, which are not limited here. If the gap D is too small, the expansion space of the nano-silicon particles 12 is small during the cycle, and the expansion stress of the nano-silicon particles 12 is too large to easily damage the resin layer 2; if the gap D is too large, the material particle size becomes larger, which affects the lithium insertion speed and dynamics.
[0036] The resin layer 2 is provided with one or more layers, for example, 1 to 4 layers can be provided. The thickness of a single layer of the resin layer 2 is greater than or equal to 20nm and less than or equal to 500nm. Specifically, the thickness of a single layer of the resin layer 2 can be 20nm, 100nm, 200nm, 300nm, 400nm, 500nm, etc., and of course, it can also be other values within the above range, which are not limited here. If the resin layer 2 is too thin, the coating effect will be weakened, and the expansion of the nano-silicon particles 12 during the cycle will destroy the resin layer 2; if the resin layer 2 is too thick, the lithium ion embedding path will increase, affecting the lithium embedding speed, and then affecting the kinetic performance.
[0037] The material of the resin layer 2 includes polyethylene, polyvinyl chloride, polypropylene, polystyrene, acrylonitrile-butadiene-styrene copolymer, natural rubber, styrene-butadiene rubber, nitrile rubber, ethylene-propylene rubber, silicone rubber, polyacrylonitrile, polyacrylic acid, sodium carboxymethyl cellulose, polyvinyl alcohol, epoxy resin, phenolic resin, polyester, unsaturated polyester resin, polyurethane and at least one low-carbon oil-based ester of the above resin derivatives.
[0038] The Dv50 of the nano-silicon particles 12 is greater than or equal to 5nm and less than or equal to 80nm. Specifically, the Dv50 of the nano-silicon particles 12 can be 5nm, 10nm, 20nm, 30nm, 40nm, 60nm, 80nm, etc., and of course it can also be other values within the above range, which is not limited here; and / or, the spacing A between the nano-silicon particles 12 is greater than or equal to 1nm and less than or equal to 20nm. Specifically, the spacing A between the nano-silicon particles 12 can be 1nm, 2nm, 5nm, 10nm, 15nm, 20nm, etc., and of course it can also be other values within the above range, which is not limited here; and / or, the Dv50 of the silicon-carbon material 1 is greater than or equal to 5nm and less than or equal to 10nm. Specifically, the Dv50 of the silicon-carbon material 1 can be 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, etc., and of course it can also be other values within the above range, No limitation is made herein; and / or, the filling degree of the nano silicon particles 12 in the porous carbon 11 is greater than or equal to 40% and less than or equal to 80%. Specifically, the filling degree of the nano silicon particles 12 in the porous carbon 11 can be 40%, 50%, 60%, 70%, 80%, etc., and of course it can also be other values within the above range, which is not limited herein; and / or, the diameter of the pores 111 of the porous carbon 11 is greater than or equal to 5nm and less than or equal to 10nm. Specifically, the diameter of the pores 111 of the porous carbon 11 can be 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, etc., and of course it can also be other values within the above range, which is not limited herein; and / or, the thickness of the porous carbon 11 is greater than or equal to 1nm and less than or equal to 3nm. Specifically, the thickness of the porous carbon 11 can be 1nm, 2nm, 3nm, etc., and of course it can also be other values within the above range, which is not limited herein.
[0039] The diameter of the pores 111 of the porous carbon 11 is greater than or equal to 5 nm and less than or equal to 10 nm. The diameter of the pores 111 of the porous carbon 11 is too small, the nano-silicon particles 12 deposited in the pores 111 of the porous carbon 11 are too few, and the material specific capacity is low; the diameter of the pores 111 of the porous carbon 11 is too large, the nano-silicon particles 12 deposited in the pores 111 of the porous carbon 11 increase, the nano-silicon particles 12 expand too much during the circulation process, and the porous carbon 11 cannot form effective constraints.
[0040] The thickness of the porous carbon 11 is greater than or equal to 1 nm and less than or equal to 3 nm. If the thickness of the porous carbon 11 is too thin, the cyclic expansion stress of the nano-silicon particles 12 is too large and the porous carbon 11 is easily damaged. If the thickness of the porous carbon 11 is too thick, the lithium ion embedding path increases, affecting the lithium embedding speed and kinetics.
[0041] The Dv50 of the nano-silicon particles 12 is greater than or equal to 5nm and less than or equal to 80nm, and / or the spacing A between the nano-silicon particles 12 is greater than or equal to 1nm and less than or equal to 20nm, and / or the Dv50 of the silicon-carbon material 1 is greater than or equal to 5nm and less than or equal to 10nm. The particle size and particle spacing of the nano-silicon particles 12 are too small, which may easily cause the agglomeration of the nano-silicon particles 12 and affect the consistency of electrical properties; the particle size of the nano-silicon particles 12 is too large, and the cyclic expansion stress is too large, which affects the cyclic consistency.
[0042] See also Figure 2 As shown, the embodiment of the present application also provides a method for preparing a negative electrode material, comprising:
[0043] Dispersing nano-silicon particles 12 in the pores 111 of the porous carbon 11 to form a silicon-carbon material 1;
[0044] The resin layer 2 is covered onto the porous carbon 11 , and a gap is provided between the resin layer 2 and the outer surface of the porous carbon 11 .
[0045] The method of dispersing the nano-silicon particles 12 in the pores 111 of the porous carbon 11 to form the silicon-carbon material 1 includes:
[0046] The nano-silicon particles 12 are deposited in the pores 111 of the porous carbon 11 by vapor deposition.
[0047] The step of covering the porous carbon 11 with the resin layer 2, with a gap between the resin layer 2 and the outer surface of the porous carbon 11, comprises:
[0048] The prepared silicon-carbon material 1 is subjected to secondary vapor deposition, and the resin layer 2 is deposited on the outer surface of the porous carbon 11 to cover the porous carbon 11 .
[0049] The embodiment of the present application also provides a negative electrode plate, comprising the above-mentioned negative electrode material or the negative electrode material prepared by the above-mentioned method.
[0050] The negative electrode plate comprises a conductive agent, an adhesive and a negative electrode current collector. The slurry formed by stirring the negative electrode material, the conductive agent and the adhesive is coated on the negative electrode current collector.
[0051] The thickness of the negative electrode sheet after rolling is greater than or equal to 20um and less than or equal to 50um. Specifically, the thickness of the negative electrode sheet after rolling can be 20um, 30um, 40um, 50um, etc., and of course it can also be other values within the above range, which is not limited here; the thickness of the negative electrode sheet after formation is greater than or equal to 24 and less than or equal to 60um. Specifically, the thickness of the negative electrode sheet after formation can be 24um, 30um, 40um, 50um, 60um, etc., and of course it can also be other values within the above range, which is not limited here.
[0052] The thickness of the negative electrode sheet after rolling is greater than or equal to 20um and less than or equal to 50um. The thickness of the negative electrode sheet after chemical formation is greater than or equal to 24 and less than or equal to 60um. The negative electrode sheet is too thin, and there are particle scratches on the negative electrode sheet, which affects the appearance of the sheet. The negative electrode sheet is too thick, which affects the dynamics and charging consistency of the battery cell.
[0053] The present application also provides a battery, including a positive electrode sheet and the above-mentioned negative electrode sheet. The battery also includes an electrolyte and a separator. The positive electrode sheet, the negative electrode sheet and the separator are wound to form a bare battery cell, which is prepared into a finished battery cell through liquid injection / chemical formation / molding.
[0054] The above is only a preferred implementation mode of the present application, and does not constitute any form of limitation to the present application. Although the present application has been disclosed as a preferred implementation mode as above, it is not used to limit the present application. Any technician familiar with this profession can make some changes or modify the technical contents disclosed above into equivalent implementation modes without departing from the scope of the technical solution of the present application. However, any simple modification, equivalent change and modification made to the above implementation modes based on the technical essence of the present application without departing from the content of the technical solution of the present application still fall within the scope of the technical solution of the present application.
Claims
1. A negative electrode material, characterized in that: include: Porous carbon; Nano silicon particles dispersed in the pores of the porous carbon; A resin layer covers the porous carbon, and a gap is provided between the resin layer and the outer surface of the porous carbon.
2. The negative electrode material according to claim 1, characterized in that The gap is greater than or equal to 100 nm and less than or equal to 600 nm.
3. The negative electrode material according to claim 1, characterized in that The resin layer is provided in one or more layers, and the thickness of a single layer of the resin layer is greater than or equal to 20 nm and less than or equal to 500 nm.
4. The negative electrode material according to claim 1, characterized in that The material of the resin layer includes polyethylene, polyvinyl chloride, polypropylene, polystyrene, acrylonitrile-butadiene-styrene copolymer, natural rubber, styrene-butadiene rubber, nitrile rubber, ethylene-propylene rubber, silicone rubber, polyacrylonitrile, polyacrylic acid, sodium carboxymethyl cellulose, polyvinyl alcohol, epoxy resin, phenolic resin, polyester, unsaturated polyester resin, polyurethane and at least one low-carbon oil-based ester of the above resin derivatives.
5. The negative electrode material according to any one of claims 1 to 4, characterized in that The Dv50 of the nano-silicon particles is greater than or equal to 5nm and less than or equal to 80nm; and / or, the spacing A between the nano-silicon particles is greater than or equal to 1nm and less than or equal to 20nm; and / or, the negative electrode material includes a silicon-carbon material, the silicon-carbon material includes the porous carbon and nano-silicon particles dispersed in the pores of the porous carbon, and the Dv50 of the silicon-carbon material is greater than or equal to 5nm and less than or equal to 10nm; and / or, the filling degree of the nano-silicon particles in the porous carbon is greater than or equal to 40% and less than or equal to 80%; and / or, the diameter of the pores of the porous carbon is greater than or equal to 5nm and less than or equal to 10nm; and / or, the thickness of the porous carbon is greater than or equal to 1nm and less than or equal to 3nm.
6. A method for preparing a negative electrode material, characterized in that: include: dispersing nano-silicon particles in the pores of porous carbon to form a silicon-carbon material; A resin layer is coated on the porous carbon, with a gap being provided between the resin layer and the outer surface of the porous carbon.
7. The method for preparing the negative electrode material according to claim 6, characterized in that: The method of dispersing nano silicon particles in the pores of porous carbon to form a silicon-carbon material comprises: Nano silicon particles are deposited in the pores of the porous carbon by vapor deposition.
8. The method for preparing the negative electrode material according to claim 6, characterized in that: The step of covering the porous carbon with a resin layer, wherein a gap is provided between the resin layer and the outer surface of the porous carbon, comprises: The prepared silicon carbon material is subjected to secondary vapor deposition, and a resin layer is deposited on the outer surface of the porous carbon to cover the porous carbon.
9. A negative electrode plate, characterized in that: The invention comprises the negative electrode material as claimed in any one of claims 1 to 5 or the negative electrode material prepared by the method as claimed in any one of claims 6 to 8.
10. The negative electrode sheet according to claim 9, characterized in that: The negative electrode plate comprises a conductive agent, an adhesive and a negative electrode current collector. The slurry formed by stirring the negative electrode material, the conductive agent and the adhesive is coated on the negative electrode current collector.
11. The negative electrode sheet according to claim 10, characterized in that: The thickness of the negative electrode sheet after rolling is greater than or equal to 20um and less than or equal to 50um, and the thickness of the negative electrode sheet after chemical formation is greater than or equal to 24 and less than or equal to 60um.
12. A battery, characterized in that: It comprises a positive electrode sheet and a negative electrode sheet as claimed in any one of claims 9 to 11.
Citation Information
Patent Citations
Silicon carbon anode material for lithium ion battery and preparation method thereof
CN110311125A
Porous core-shell structure silicon-carbon negative electrode material for lithium ion battery and preparation method thereof
CN111146430A
Silicon-carbon negative electrode material, preparation method and battery
CN116130637A